A dietary intervention for vasomotor symptoms of menopause: a randomized, controlled trial. Issue 1 (16th January 2023) - Barnard, Neal D.; Kahleova, Hana; Holtz, Danielle N.; Znayenko-Miller, Tatiana; Sutton, Macy; Holubkov, Richard; Zhao, Xueheng; Galandi, Stephanie; Setchell, Kenneth D. R.
Abstract : A dietary intervention consisting of a plant-based diet, minimizing oils, and daily soybeans significantly reduced the frequency and severity of postmenopausal hot flashes and associated symptoms. Abstract: Objective: Postmenopausal vasomotor symptoms disrupt quality of life. This study tested the effects of a dietary intervention on vasomotor symptoms and menopause-related quality of life. Methods: Postmenopausal women (n = 84) reporting at least two moderate-to-severe hot flashes daily were randomly assigned, in two successive cohorts, to an intervention including a low-fat, vegan diet and cooked soybeans (½ cup [86 g] daily) or to a control group making no dietary changes. During a 12-week period, a mobile application was used to record hot flashes (frequency and severity), and vasomotor, psychosocial, physical, and sexual symptoms were assessed with the Menopause-Specific Quality of Life questionnaire. Between-group differences were assessed for continuous ( t tests) and binary ( χ 2 /McNemar tests) outcomes. In a study subsample, urinary equol was measured after the consumption of ½ cup (86 g) of cooked whole soybeans twice daily for 3 days. Results: In the intervention group, moderate-to-severe hot flashes decreased by 88% ( P < 0.001) compared with 34% for the control group ( P < 0.001; between-group P < 0.001). At 12 weeks, 50% of completers in the intervention group reported no moderate-to-severe hot flashes at all. Among controls, there was no change in this variable from baseline ( χ 2 test, P < 0.001). Neither seasonality nor equol production status was associated with the degree of improvement. The intervention group reported greater reductions in the Menopause-Specific Quality of Life questionnaire vasomotor ( P = 0.004), physical ( P = 0.01), and sexual ( P = 0.03) domains. Conclusions: A dietary intervention consisting of a plant-based diet, minimizing oils, and daily soybeans significantly reduced the frequency and severity of postmenopausal hot flashes and associated symptoms.